Resultados de um programa piloto de desestigmatização de saúde mental juvenil - Gonçalves, M.; Moleiro, C. (Revista Portuguesa de Saúde Pública, 2016)
Introduction Stigma remains a significant barrier to the effective promotion of youth mental health. Stigma has been associated negatively with the mental health care. Objective The aim of this article is to present the results of a pilot test of an intervention for the de‐stigmatization of mental health based on video administered in the school environment (N = 207). Method The classrooms of a school were randomized to the intervention and control group in the study, all students in each classroom belonging to the same group. Adolescents in the treatment group were shown a video touching on issues such as the stigma of mental health care exposed by a young peer. Both intervention and control groups were evaluated at three different times ‐ pre, post and 1 month of follow‐up with the following three instruments adapted with permission of their authors: Self Stigma of Seeking Help Scale (SSOSH) of Vogel et al., Social Stigma for Receiving Psychological Help Scale (SSRPH) of Komiya et al. and Attribution Questionnaire‐Children form (AQ‐8c) of Corrigan. Results The intervention significantly reduced scores in the three scales for the treatment group post‐intervention. This decline in scores within the treatment group was significantly greater than the decline in values observed in the control group. The decrease stigma remained higher for the treatment group than for the control group at follow‐up, although these results did not reach statistical significance. After adjusting for socio‐economic indicators, grade and gender, significant intervention effects were identified in the post in self‐stigma and in seeking help. Conclusion Stigma plays a big role in unmet need for mental health care. In addition to lowering the access to mental health care, stigma can also harm directly adolescents by reducing self‐esteem. The importance of developing a rapid response and low cost of reducing stigma is critical to improve access to mental health treatment for those in need of it.